SPAIN’S STRUGGLE AND STRATEGY: UNVEILING THE ROLE IN WORLD WARS (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article provides a comprehensive exploration of Spain’s involvement, struggles, and strategic decisions during the tumultuous periods of World War I and World War II. Delving into historical records and primary sources, the author aims to shed light on Spain’s often overlooked and nuanced role in these global conflicts. The article begins by establishing the geopolitical context of Spain during the early 20th century, examining the internal dynamics of the country, including its political landscape, economic conditions, and social factors. By doing so, the author lays the groundwork for a deeper understanding of Spain’s choices and constraints during the turbulent times of both World Wars.